IMPLEMENTATION OF OFFICE MANAGEMENT EFFICIENCY AT PT RAJAWALI NUSINDO MADIUN BRANCH - Fadhilla Auliya, Nanda; Prihatinta, Triana (Politeknik Negeri Madiun, 2025)
One form of success of an organization/company in implementing office activities by increasing productivity, cost usage, and helping to optimize time and resources as a form of efficiency measurement. This study uses a qualitative descriptive method. The results of the study obtained indicate that the implementation of office management efficiency at PT Rajawali Nusindo has been carried out with the implementation of the five principles of office management efficiency, the principle of planning is the preparation of the RKAP, the principle of simplification is the application of e-office to help handle letters, the principle of saving is no duplication of files, the principle of elimination is the elimination of activity steps that switch to the use of office applications such as e-office, and the principle of merging with the existence of a multi-function printer machine that can do several activities, namely printing, duplicating, and scanning files.